Guidelines for the analysis of mathematics textbooks lessons on the subject of proportionality - Castillo Céspedes, María José (2022)
The objective of this study is the construction of a guideline of indicators of didactic suitability related to the topic of proportionality, which can be used as a basis for the analysis and evaluation of textbook lessons, and as a resource for teachers’ reflection on effectively implemented instructional processes about proportionality. Since the study of proportional reasoning has become a relevant field of research in mathematics education, it is possible to identify specific suitability criteria for guiding the teaching and learning processes, applying the methodology of content analysis to a bibliographic review of key research in this area. Various aspects, components, and indicators of the notion of didactic suitability guide the selection and categorization of didactic-mathematical knowledge about proportionality in elementary and secondary education derived from research about such content. Finally, a Mathematics Textbook Lesson Analysis Guide adapted to the topic of proportionality was created. Since the textbook contains curricular material that largely determines what happens in the classroom and acts as a mediator in student learning, and ratios, proportions, and proportionality are studied in the curricula of elementary and secondary education, the Guide obtained can be a valuable resource for teachers. It is necessary to design and implement training actions with teachers that they are familiar with and can use competently, bearing in mind that there is always room for further improvement.